In search of apprehending customers' value perception - Beata Stępień (International Journal of Management and Economics, 2017)
The article clarifies the concept of value for customer, demonstrates challenges related to the concept itself and its measurement and sheds new light on the consequences of conceptual and metric choices. The analysis focuses on three points: first, it shows, how the definition and delineation of customer perceived value (CVP) implies the choice of certain measurement tools, but does not necessarily reveal the essence of the measured construct. Second, it provides a quantitative measure of CVP components showing the functional interconnections between them without presenting their causal relations. Third, it suggests the priority of a theoretical conceptualization over any technical craft considerations in CVP measurement. The article begins with mapping and deconstructing the value concept, which is followed by a critical discussion of its measurement challenges. Mixed methodology for empirical exploration of CVP construct is recommended here, being as the approach that blends quantitative methods with a deeper understanding of CVP provided by qualitative tools.
Keywords: D01; D12; M30; M31; 650; value for customer; customer perceived value; customer value perception; value measurement; value dimensions; value components